New tricks. Season one [videorecording (DVD)] - Cronk, Gina; Mitchell, Roy; Block, Simon; Fisher, Nic; Hume, Alison; McHale, Tony; Seed, Paul; Payne, Jamie; East, Jon; Redman, Amanda, 1957-; Bolam, James, 1935-; Armstrong, Alun; et al. (New tricks (Television program), 2009)
As punishment for messing up a kidnap rescue and shooting a dog in the process, Detective Superintendent Sandra Pullman is re-assigned to the newly created unsolved murder squad. Due to a manpower shortage her team is made up of veteran detectives brought back onto the police force, bringing a 1970's mentality to modern policing. The team's first case is to re-investigate a twenty year old murder conviction which has suddenly come into question due to police corruption. Sifting through the lies, dubious motives and the police cover up during the first investigation, the unorthodox methods of the dinosaur detectives eventually discover what really happened twenty years ago. In the process, the squad clears up two murders and an armed robbery.